The Impact of Covid-19 on The Social and Cultural Life of The Balinese Community from The Perspective of Hinduism Education - Adhitya Gangga, I Gusti Bagus; Sariani Binawati, Ni Wayan (International Journal of Multidisciplinary Sciences, 2023)
The Coronavirus (Covid -19) has been declared a Pandemic by the World Health Organization or what is called the World Health Organizer (WHO), because it has spread to almost all countries in the world. Efforts to contain the spread of this virus are continuously being carried out, but in implementation it is inevitable that new impacts or problems will arise in the adjustment. It is very important for us to understand the impact of the arrival of Covid-19 on the socio-cultural life of the Balinese people so that the government does not only focus on preventing the transmission of Covid-19, but also on the sustainability of the socio-cultural life of the Balinese people which may not work due to the policies implemented. The purpose of this research was to provide an overview and explanation of the nature of the Corona virus and Hinduism education as a way of responding to the current pandemic situation. This research was carried out in Bali.  The approach in this study was a descriptive qualitative approach, which explained the picture of the socio-cultural life of the Balinese Hindu community in the midst of the Covid -19 Pandemic. This study aimed to determine the effects of the Covid-19 Pandemic so that it can be used as learning in the future to face similar disasters. The effects of this Pandemic were also studied from the perspective of Hinduism education.  As a result of the arrival of the Covid -19, many significant changes have occurred in Bali.  The results showed that the socio-cultural life of the Balinese people followed new adjustments or adaptations to anticipate the development of the Covid-19 outbreak. These adjustments include regulations, religious activities (regarding traditions) and social activities.